2003
DOI: 10.1002/clc.4960261208
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma thioredoxin in patients with acute myocardial infarction

Abstract: SummaryBackground and hypothesis: Thioredoxin is an important biomarker for oxidative stress. We investigated whether thioredoxin levels were elevated in patients with acute myocardial infarction (AMI) and were associated with the results of coronary reperfusion.Methods: The present study determined plasma thioredoxin levels in 51 patients with AMI, 30 patients with stable exertional angina (SEA), and 30 patients with chest pain syndrome (CPS). Plasma sampling was performed on admission, at 12 h, 1 week, 2 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…We have previously reported that the levels of thioredoxin were elevated in patients with acute coronary syndrome including AMI or unstable angina (25)(26)(27). In the present study we showed that the levels of thioredoxin were significantly higher in patients with CAD than those without CAD.…”
Section: Discussionsupporting
confidence: 65%
“…We have previously reported that the levels of thioredoxin were elevated in patients with acute coronary syndrome including AMI or unstable angina (25)(26)(27). In the present study we showed that the levels of thioredoxin were significantly higher in patients with CAD than those without CAD.…”
Section: Discussionsupporting
confidence: 65%
“…In the clinical setting, we have previously investigated the correlation between ROS generation and coronary heart disease. [32][33][34][35] Our previous studies have demonstrated that oxidative stress markers, including plasma thioredoxin levels, urinary biopyrrins and 8-hydroxy-2'-deoxyguanosine excretion, were elevated in patients with AMI. We have previously reported that increased ROS may predict subsequent cardiovascular events; however, it was still unknown whether edaravone administration reduces ROS generation during the clinical course of AMI in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma Trx-1 levels are elevated in patients with unstable angina, spastic angina, and acute myocardial infraction compared with those in stable exertional angina and chest-pain syndrome (61,120,165). Elevated Trx-1 levels in acute myocardial infraction are associated with hyperaggregation of platelet, which indicates further risk as well as pathogenesis of ischemic heart diseases (123).…”
Section: Thioredoxin-glutaredoxin and Related Molecules As Biomarkersmentioning
confidence: 99%
“…The mitochondrial protein SP-22 exerts its cardioprotective effect in rat heart as an antioxidant molecule (5). However, the higher expression level of serum or plasma Trx-1 is indicative of a risk factor for the patients with acute myocardial infarction (AMI), in which Trx-1 could enhance platelet aggregability and reduce the left ventricular ejection fraction (123,165).…”
Section: Ischemic Heart Diseasesmentioning
confidence: 99%